The Assessment of Motivation in the Learning of EFL at University Level: Validation of the English Language Learning Motivation Scale (ELLMS) at Four Spanish State Universities - María del Carmen Garrido-Hornos (Revista Alicantina de Estudios Ingleses, 2023)
Successful performance in the study of English as a Foreign Language is known to be subject to psychological constructs such as type of motivation, degree of self-regulated learning and levels of anxiety and burnout, or academic fatigue. The present study—conducted at the University of Valladolid Segovia Campus—served a double purpose. Firstly, it was used to validate the English Language Learner Motivation Scale (ELLMS) in a sample of university students who were studying this language but whose degrees were in subjects other than English Language or Linguistics. Secondly, it demonstrated that intrinsic motivation is associated with less anxiety and greater self-regulation and self-efficacy in the English language learning process. To both ends, we created a 94-question online survey which blended items from four other instruments measuring levels of anxiety, self-regulation and burnout. This questionnaire, delivered to 214 students from four different Spanish universities, produced interesting results. To begin with, it confirmed the first objective of the study and validated ELLMS as a viable instrument to measure motivation in this population, as well as confirming the presence of the three psychological factors envisaged in the original theoretical proposal and which the reader can find defined and analysed in depth in this paper: intrinsic motivation, external regulation and introjected regulation. The variable introjected regulation was negatively correlated with anxiety but positively with reported levels of burnout informed. With regard to external regulation, the results were not conclusive. This paper considers both the educational implications of these results and the impact that these variables have on the learning of English as a Foreign Language.